Peritoneal dialysis in patients with refractory congestive heart failure - Raymond Azar; Arielle Desitter; Marion Guillou; Justine Schricke; Manon Geeraert (RDPLF, 2022)
Chronic heart failure is a growing problem. Despite progress in its management, many patients become refractory to therapies including diuretic resistance, major congestion, and worsening renal function. The only alternative to get rid of excess water and sodium is ultrafiltration, which can be achieved via hemodialysis or peritoneal dialysis (PD). The majority of studies have shown multiple benefits of PD as an improvement in functional class, a reduction in hospitalization leading to increased quality of life, and even a reduction in mortality. Being a home dialysis technique, it is more favorably accepted by patients. It remains necessary to confirm these potential positive outcomes and to identify patients who would benefit the most from this treatment in the era of new therapies available to date.